Phénoménotechnique du temps et cosmogonie scientifique - Cohen-Tannoudji, Gilles; Gazeau, Jean-Pierre (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
The coming together of the two great scientific disciplines of the 20th century, particle physics and cosmology, each of which has developed a robust standard model, has led to the birth of an authentic scientific theory of the beginnings of the universe. Such a theory, based on quantum (micro)physics, can serve as a framework for the theoretical thinking of time in contemporary science. On these premeses, the contribution will argue that the phenomenotechnics of time, based on a reading of Bachelard’s Noumène et microphysique, Georges Lemaître’s book L’hypothèse de l’atome primitif – Essai de cosmogonie and its preface by Ferdinand Gonseth, can provide the methodological framework to meet the challenge of a scientific cosmogony, whose standard model would result from the consolidation of these two standard models.